2016
DOI: 10.1074/jbc.m116.720243
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ral GTPases Using a Stapled Peptide Approach

Abstract: Aberrant Ras signaling drives numerous cancers, and drugs to inhibit this are urgently required. This compelling clinical need combined with recent innovations in drug discovery including the advent of biologic therapeutic agents, has propelled Ras back to the forefront of targeting efforts. Activated Ras has proved extremely difficult to target directly, and the focus has moved to the main downstream Ras-signaling pathways. In particular, the Ras-Raf and Ras-PI3K pathways have provided conspicuous enzyme ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 56 publications
(97 reference statements)
1
30
0
Order By: Relevance
“…For example, one study reported the use of a structure-based approach to inhibit Ral GTPases [8]. A stapled peptide approach was also reported to regulate RalA and RalB [20]. However, these approaches have not shown considerable clinical promise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study reported the use of a structure-based approach to inhibit Ral GTPases [8]. A stapled peptide approach was also reported to regulate RalA and RalB [20]. However, these approaches have not shown considerable clinical promise.…”
Section: Discussionmentioning
confidence: 99%
“…Small noncoding RNA molecules (19)(20)(21)(22) nucleotides in length) known as microRNAs (miRNAs) were found to act as endogenous suppressors of gene expression by binding to the 3' untranslated region (UTR) of mRNAs [4]. Many studies have shown that miRNAs play an important role in many biological processes of tumors, such as proliferation, differentiation, apoptosis and invasion [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is speculated that this effect of DHA may be a common phenomenon in tumor cells. Consistently, one group selectively designed RalB peptide inhibitors in that Ras-Ral pathway is difficult disrupted by traditional medicine [50]. The RalB-specific ubiquitin ligase, USP33 is a member of the USP deubiquitinase superfamily and controls the ubiquitylation of RalB GTPase at Lys 47, which provides a regulatory switch to trigger the autophagy or innate immune response in macrophages [8].…”
Section: Discussionmentioning
confidence: 99%
“…Stapled peptides based on a helix from the RASGEF son of sevenless (SOS) has been used to target RAS. By using the RAL binding domain of RALBP1 as a template, the Mott group designed an a-helical stapled peptide that can bind selectively to active RALB-GTP and block downstream effector signaling of RAL (Thomas et al, 2016). These peptides bind to the switch I and II regions of RAL, which are the sites of interaction with RAL effectors like RALBP1 and regulators like RALGEF.…”
Section: B Targeting Ral Directlymentioning
confidence: 99%